The Effect of Profitability, Leverage and Liquidity on Dividend Policy for Construction Issuers in 2014-2019 - Althov Feizal, Dava; Sudjono, Sudjono; Badawi Saluy, Ahmad (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The era of globalization when it has led to the development of the economy which is very rapid and demanding companies , both companies locally and internationally , must contend tight . Policy dividends have become a concern many parties on the outside of the internal enterprise , such as the holder of the stock , investors, creditors , and the external others who have interest in the information that is issued by a company. This paper aims to determine the factors that affect dividends in construction companies . To test the hypothesis , we used the data series while the annual are listed on the bursary effect in 2014 until 2019. We use panel data model to analyze the influence of Return On Equity , Debt to Equiy Ratio and Current Ratio that affect the dividend.